Rapid Detection of Group B Streptococcus and Escherichia coli in Amniotic Fluid Using Real-Time Fluorescent PCR. Issue 3 (2004) - Straka, Michele; Cruz, Wifred Dela; Blackmon, Camille; Johnson, Oswald; Stassen, Sara; Streitman, David; Golden, Stephen; Stamilio, David
Abstract : Objective: To establish reliability and validity of real-time fluorescent PCR for early detection of bacterial invasion of the amniotic cavity. Methods: Amniotic fluid samples from 40 patients undergoing mid-trimester genetic amniocentesis were incubated for 6 h at 37℃ and were cultured on media specific for group B streptococcus (GBS) and E. coli. Concurrently, samples were analyzed with real-time fluorescent PCR (Roche LightCycler) using DNA primers and probes designed to detect the CAMP factor encoding cfb gene and uidA gene of GBS and E. coli, respectively. For positive control and to simulate amniotic fluid colonization, 104 cfu/ml of GBS and E. coli were inoculated on sterile amniotic fluid and incubated for 6 h. Bacterial genomic DNA for the two organisms was extracted and purified via the two-step precipitation method using a commercial kit. The real-time PCR assays were also tested against 25 non-GBS and non- E. coli bacterial species. The lower limit of detection for each pathogen was established using serial dilution of bacterial genomic DNA. Results: All patient samples were negative for evidence of GBS and E. coli with both culture and real-time PCR methods. Amniotic fluid samples inoculated with GBS and E. coli were positive with real-time PCR whereas the 25 bacterial species other than GBS or E. coli tested negative with the assay. Average total sample processing time including the pre-enrichment step was 7 h 40 min. The average cost for DNA extraction and PCR testing was 8.50 per test. Conclusion: Real-time fluorescent PCR is a valid and reliable method for detection of specific pathogens in amniotic fluid. This technique is sensitive for low inoculation levels. Real-time fluorescent PCR has potential to impact clinical management as a rapid, reliable detection method for GBS and E. coli in chorioamnionitis.